SYSTEMATIC LITERATURE REVIEW: HUBUNGAN ANTARA PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP DISPOSISI MATEMATIS - Lidia, Lidia; Rahayu, Wardani; Meiliasari, Meiliasari (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Realistik Mathematics Education (RME) stems from the understanding that mathematics is a human activity, with the main goal being to facilitate the transition from informal to formal knowledge through problem-solving in a real-world context. The purpose of this study is to conduct literary analysis related to the relationship between RME and mathematical disposition. Systematic Literature Review (SLR) is the method used. Data collection is carried out by documenting and reviewing every article about the relationship between mathematical and RME dispositions that have this research as part of it. A total of sixteen articles from Google Schoolar, Scopus, and ERIC were used in this experiment. RME is a term used in mathematics that has been published from 2014 to 2024. The study's findings indicate a positive correlation between the RME paradigm and mathematical disposition. Pendekatan RME is also effective in enhancing students' abilities in a constructive way and fostering their self-confidence in the context of mathematical education. Later, mathematical aptitude continues to be the primary factor in enhancing a particular problem in RME.